Search for Excited u and d Quarks in Dijet Final States at Future pp Colliders - Ahmet Nuri Akay; Yusuf Oguzhan Günaydin; Mehmet Sahin; Saleh Sultansoy (Advances in High Energy Physics)
Resonant production of excited u and d quarks at the Future Circular Collider and Super Proton-Proton Collider has been researched. Dominant jet-jet decay mode has been considered. It is shown that FCC and SppC have great potential for discovery of excited u (d) quark: up to 44.1 (36.3) and 58.4 (47.8) TeV masses, respectively. For degenerate case (Mu⋆ = Md⋆), these values are 45.9 and 60.9 TeV, respectively. This discovery will also afford an opportunity to determine the compositeness scale up to multi-PeV level.